2012
DOI: 10.1017/s1368980012002650
|View full text |Cite
|
Sign up to set email alerts
|

‘I don't have to go to the gym because I ate very healthy today’: the development of a scale to assess diet-related compensatory health beliefs

Abstract: ObjectiveNutritional interventions to decrease energy intake, aimed at portion sizes and front-of-package labelling, are effective only if people do not compensate for their reduced energy intake. Since several observational studies indicate that these interventions could prompt compensation behaviour, it is important to assess underlying beliefs. Therefore, the purpose of the two studies reported here was to develop a Diet-related Compensatory Health Beliefs Scale (Diet-CHBS).DesignCross-sectional surveys wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Low internal consistency does not mean, however, that heterogeneous constructs are less valid (Dunn, Baguley, & Brunsden, ). In contrast to former research (Poelman, Vermeer, Vyth, & Steenhuis, ), we included the healthy behaviour (i.e., compensatory behaviour) in the item stem and asked for different unhealthy behaviours. Although this reversed measurement is very similar to outcome expectancies, bivariate correlations between CHBs and outcome expectancies suggest that both constructs share only little variance.…”
Section: Discussionmentioning
confidence: 99%
“…Low internal consistency does not mean, however, that heterogeneous constructs are less valid (Dunn, Baguley, & Brunsden, ). In contrast to former research (Poelman, Vermeer, Vyth, & Steenhuis, ), we included the healthy behaviour (i.e., compensatory behaviour) in the item stem and asked for different unhealthy behaviours. Although this reversed measurement is very similar to outcome expectancies, bivariate correlations between CHBs and outcome expectancies suggest that both constructs share only little variance.…”
Section: Discussionmentioning
confidence: 99%
“…However, maintaining the intention not eating candy helps him to alter the rewarding stimuli of the candy with the reward by the physical activity itself like feeling more relaxed or happy. In previous studies, CCs found to correlate positively with risk behaviors and symptoms [20][21][22] , to determine self-regulation failure and lower goal-attainment [23] . In addition, CCs have been associated with fewer health behaviors and motivational stage movements [22] .…”
Section: Compensatory Cognitionsmentioning
confidence: 99%
“…A number of instruments have been designed to measure compensatory health beliefs for a range of behavior “pairings” [17,19], including those that exist between food and exercise [20,21]. However, these measures may not fully capture the specific “licensing” relationship that exists between exercise and subsequent unhealthy snacking behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, compensatory health belief items around weight management, originally stemming from the Compensatory Health Beliefs Scale [17], and subsequently used by Radtke et al [21], only include one item addressing the “food-and-exercise” pairing. In addition, although the instrument used by Poelman, Vermeer, Vyth and Steenhuis [20] contains four items assessing this pairing, these items focus on how a healthy diet/smaller portion sizes can compensate for minimal exercise (e.g., “When I eat less, it’s not necessary to have a lot of exercise”), rather than how exercise may act as justification for unhealthy eating/drinking (e.g., “because I have exercised, it’s okay to eat some chocolate cake”).…”
Section: Introductionmentioning
confidence: 99%